Das Europäische Parlament. Institution, Vision und Wirklichkeit - Dialer, Doris (Europawissenschaftliche Reihe, 2010)
"In May 2014 the 8th European elections take place. 751 Members of Parliament form 28 different countries are directly elected for a five-year term form an electorate of 383 Mio citizens. The European Parliament is a dynamic, truly supranational and since Lisbon a more and more powerful actor. It negotiates on eye-level with the Council of Ministers, holds the European Commission effectively accountable, represents the aggregated interests, ideas and concerns of the Union's citizens, and supervises the development of the EU together with the national parliaments. As a global player the European Parliament deals with members of parliaments of third countries, negotiates international agreements and watches over the protection of human rights and democracy. The authors - MEPs, officials, stakeholders and experts - gibe a deep practical and academic insight into all functions of the European Parliament. The different articles take into account the specific conditions of the EU's only directly legitimized institution. For academics and practitioners alike, Dialer, Neisser and Lichtenberger offer a superb ""guide"" for any serious understanding of the world's only elected transnational parliament." Authors: Doris Dialer, Eva Lichtenberger, Heinrich Neisser, Jerzy Buzek, Wolfgang Hiller, Elmar Brok, Flooh Perlot, Eva Zeglovits, Peter Plaikner, Herbert Reul, Albert Deß, Alexander Alvaro, Vanessa Aulehla, Olaf Münichsdorfer, Heike Merten, Othmar Karas, Jürgen Mittag, Julia Krüger, Christa Prets, Margarethe Richter, Michael Gahler, Gerrit F. Schlomach, Stefan Pﬁ tzner, Erika Mann, Oliver Rolofs, Stefan Schennach, Thomas Mann, Marco Reuter,